Gambaran Pengetahuan dan Sikap Remaja Putri terhadap Kesehatan Reproduksi pada Siswi SMP Negeri 1 Ubud di Kabupaten Gianyar - Cokorda Istri Swandewi Puspasari Putri; Luh Gede Pradnyawati; Komang Trisna Sumadewi (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Reproductive health on adolescents in Indonesia must be considered more seriously, because more than 20% of Indonesia's population is aged 10-18 years. In Bali, adolescent females' reproductive health has only gotten little attention. There are only few reproductive health materials in schools, and adolescence have lack awareness about reproductive health. Adolescent attitudes about reproductive health will be influenced by these lack of understanding and information. The purpose of this study is to describe the knowledge and attitudes of adolescent girls towards reproductive health in students of SMP Negeri 1 Ubud in Gianyar Regency. This study employed a cross-sectional, descriptive quantitative methodology to gather primary data through questionnaires. The sampling method was Systematic Random Sampling with a sample of 106 students from class VII, VIII, and IX. The results of this study indicate that respondents who have good knowledge have the largest percentage of 67 respondents (63.2%), while the attitudes of respondents in this study more than half still have negative attitudes, namely 54 respondents (50.9%). Therefore, it can be concluded that most students have good knowledge, but their attitudes still negative towards reproductive health. Keywords: reproductive health, adolescent girls, knowledge, attitude, cross-sectional